Factors associated with polyacrylamide hydrogel outcomes in women with stress urinary incontinence. Issue 3 (25th January 2023) - Hoe, Venetia; Yao, Henry H.; Gough, Karla; O'Connell, Helen E.
Abstract: Knowledge of factors associated with superior outcomes in women treated with urethral bulking agents for stress urinary incontinence (SUI) remains limited. The aim of this study was to examine associations between post‐treatment outcomes in women who had undergone polyacrylamide hydrogel injections for SUI, and physiological and self‐reported variables captured during pre‐treatment clinical evaluation. A cross‐sectional study was undertaken in female patients treated for SUI with polyacrylamide hydrogel injections by a single urologist between January 2012 and December 2019. Post‐treatment outcome data were gathered in July 2020 using the Patient Global Impression of Improvement (PGI‐I), Urinary Distress Inventory‐short form (UDI‐6), Incontinence Impact Questionnaire (IIQ7), and International Consultation on Incontinence Questionnaire Short Form (ICIQ SF). All other data were gathered from women's medical records including pre‐treatment patient‐reported outcomes. Associations between post‐treatment outcomes and pre‐treatment physiological and self‐reported variables were investigated using regression models. One hundred seven of the 123 eligible patients completed post‐treatment patient‐reported outcome measures. Mean age was 63.1 years (range 25–93 years), and median time between first injection and follow‐up was 51 months (inter‐quartile range 23.5–70 months). Fifty‐five (51%) women had a successful outcome based on PGI‐I scores. Women with type 3 urethral hypermobility pre‐treatment were more likely to report treatment success (PGI‐I). Poor bladder compliance pre‐treatment was associated with greater urinary distress, frequency and severity (UDI‐6 and ICIQ) post‐treatment. Older age was associated with worse urinary frequency and severity (ICIQ) post‐treatment. Associations between patient‐reported outcomes and time between first injection and follow‐up were trivial and not statistically significant. Severity of pre‐treatment incontinence impact (IIQ‐7) was associated with worse incontinence impact post‐treatment. Type 3 urethral hypermobility was associated with a successful outcome, whereas pre‐treatment incontinence impact, poor bladder compliance and older age were associated with poorer self‐reported outcomes. Long‐term efficacy appears to hold in those who responded to initial treatment.